KONSELING ISLAM DENGAN PENDEKATAN SOLUTION FOCUSED BRIEF THERAPY (SFBT) UNTUK MENGATASI KECEMASAN IBU MUDA PASCA MELAHIRKAN [ISLAMIC COUNSELING WITH A SOLUTION FOCUSED BRIEF THERAPY (SFBT) APPROACH TO OVERCOME ANXIETY OF YOUNG MOTHERS POST-BIRTH] - Arif Widodo; N Nurjannah (Perkumpulan Ahli Bimbingan Konseling Islam (PABKI) Indonesia, 2022)
This study aims to determine how the application of Islamic counseling with the Solution Focused Brief Therapy (SFBT) approach to overcome the anxiety of young mothers after giving birth. The research uses qualitative research methods with the type of case study research. The data collection techniques were carried out by observation and interview techniques. The results of the application of Islamic counseling with the Solution Focused Brief Therapy (SFBT) approach to dealing with anxiety in ZM counselees can be seen from the ZM counseling feeling better and being able to control their thoughts when anxiety arises. The counselee also felt more relieved, calm, and relaxed after attending the counseling session. However, the researcher does not deny that sometimes the counselee still finds it difficult to control his anxiety, but the counselee soon realizes that this anxiety can interfere with his life and can refocus on being able to regulate his thoughts and emotions so that he can overcome his anxiety.